Current knowledges in pharmaconutrition: “Ketogenics” in pediatric gliomas - Cecchi, Nicola; Romanelli, Roberta; Ricevuti, Flavia; Amitrano, Marianna; Carbone, Maria Grazia; Dinardo, Michele; Burgio, Ernesto (Frontiers in Nutrition, 2023)
Brain tumors account for 20-25% of pediatric cancers. Gliomas are the most frequent type of brain tumor, classified from grade I to grade IV according to the rate of malignancy. Current treatments for gliomas use chemotherapy, radiotherapy, tyrosine kinase inhibitors, monoclonal antibodies and surgery, but each of the treatment strategies has several serious side effects. Therefore, to improve treatment efficacy, it is necessary to tailor therapies to patient and tumor characteristics, using appropriate molecular targets. An increasingly popular strategy is pharmaconutrition, which combines a tailored pharmacological treatment with a diet designed to synergize the effects of drugs. In this review we deal in the molecular mechanisms, the epigenetic effects and modulation of the oxidative stress pathway of ketogenic diets, that underlie its possible role, in the treatment of infantile brain tumors, as a complementary approach to standard cancer therapy.